2013
DOI: 10.20343/teachlearninqu.1.1.113
|View full text |Cite
|
Sign up to set email alerts
|

One Important Lesson I’ve Learned from My Involvement with SoTL

Abstract: Teaching and Learning and professor in the School of business at queen's university in Canada. Joy has also served as the president of the Society for Teaching and Learning in higher education, and is the co-editor of Taking Stock: Research on Teaching and Learning in Higher Education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Earlier research (Marquis ) indicated that effective SoTL institutes work to bring together and support a diverse range of scholars, creating a community of practice that both enhances the work conducted and helps individuals advocate for it within institutional cultures that can be unsupportive of teaching and learning inquiry (Mighty ). Nonetheless, this research also pointed out that such communities can be difficult to develop and sustain, particularly given demands on scholars’ time (Brew ) and the fact that SoTL is often not rewarded or recognized in considerations of career progress (Walker, Baepler, and Cohen ).…”
Section: The Establishment Of Miietl Research Fellowsmentioning
confidence: 99%
“…Earlier research (Marquis ) indicated that effective SoTL institutes work to bring together and support a diverse range of scholars, creating a community of practice that both enhances the work conducted and helps individuals advocate for it within institutional cultures that can be unsupportive of teaching and learning inquiry (Mighty ). Nonetheless, this research also pointed out that such communities can be difficult to develop and sustain, particularly given demands on scholars’ time (Brew ) and the fact that SoTL is often not rewarded or recognized in considerations of career progress (Walker, Baepler, and Cohen ).…”
Section: The Establishment Of Miietl Research Fellowsmentioning
confidence: 99%
“…During this time, we lamented how disappointing it can be to leave the excitement and energy of a conference and return to our isolated offices in the corners of our institutions. This can be particularly difficult for those involved in the Scholarship of Teaching and Learning (SoTL) who feel unsupported and disconnected from their research-intensive colleagues (Mighty, 2013;Roxå & Mårtensson, 2009, 2012. In fact, this had been Michelle's experience at two previous ISSOTL conferences, which made her particularly determined not to let it happen again.…”
mentioning
confidence: 99%
“…In this reflection, we offer a narrative of the process we undertook to form and maintain our group, and we consider how it enabled us to continue our SoTL-focused conversations well after returning home from the ISSOTL conference. Given the oft-felt isolation of practitioners of SoTL even after they have made connections with colleagues at a valuable conference, we find the opportunity to share this experience important (Mighty, 2013;Roxå & Mårtensson, 2009, 2012. This reflection is grounded in research literature and explains the approach we took, the benefits and challenges we experienced, and the principles we uncovered.…”
mentioning
confidence: 99%